2019
DOI: 10.1371/journal.pbio.3000286
|View full text |Cite
|
Sign up to set email alerts
|

Specific activation of pro-Infliximab enhances selectivity and safety of rheumatoid arthritis therapy

Abstract: During rheumatoid arthritis (RA) treatment, long-term injection of antitumor necrosis factor α antibodies (anti-TNFα Abs) may induce on-target toxicities, including severe infections (tuberculosis [TB] or septic arthritis) and malignancy. Here, we used an immunoglobulin G1 (IgG1) hinge as an Ab lock to cover the TNFα-binding site of Infliximab by linking it with matrix metalloproteinase (MMP) -2/9 substrate to generate pro-Infliximab that can be specifically activated in the RA region to enhance the selectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 44 publications
0
25
0
1
Order By: Relevance
“…Three weeks after intravenous inoculation of 1.5×10ˆ6 p401 PDX tumor cells/mouse, we injected CLL-1 CAR +iC9-IL15 CAR T cells (2.5×10ˆ6/mouse) T cells ( figure 5A ), followed by intravenous injections of anti-TNFα. 24 25 The TNFα levels were significantly reduced in mice treated with the first dose of anti-TNFα ( figure 5B ) but were not well controlled by subsequent injections. This treatment had no adverse effect on T cell expansion or tumor control ( figure 5C ).…”
Section: Resultsmentioning
confidence: 96%
“…Three weeks after intravenous inoculation of 1.5×10ˆ6 p401 PDX tumor cells/mouse, we injected CLL-1 CAR +iC9-IL15 CAR T cells (2.5×10ˆ6/mouse) T cells ( figure 5A ), followed by intravenous injections of anti-TNFα. 24 25 The TNFα levels were significantly reduced in mice treated with the first dose of anti-TNFα ( figure 5B ) but were not well controlled by subsequent injections. This treatment had no adverse effect on T cell expansion or tumor control ( figure 5C ).…”
Section: Resultsmentioning
confidence: 96%
“…Starting drug treatment in the early stage can effectively prevent the progression of the disease and reduce the rate of disease development. Because a large number of reports on the regenerative function of Treg cells have been published and the ideal treatment strategy is to induce self-tolerance before obvious tissue damage occurs, researchers have designed various strategies ways to increase the number of Treg cells and restore their function(101)(102)(103)(104)(105)(106)(107), by enhancing the function of Treg cells in vivo, including reducing the pro-inflammatory environment and enhancing the response of effector cells to inhibition (108-113) (Table…”
mentioning
confidence: 99%
“…[4] These clinical ndings indicated that preventing the interference effect of anti-Id Ab can solve many of the clinical problems of Ab drugs. Our team have demonstrated that the spatial hindrance-based Ab lock can prevent the response of anti-Id Ab to In iximab (anti-I-Id Ab); the binding of the anti-I-Id Ab to pro-In iximab was 108-fold weaker than that to In iximab [19], and the Ab lock maintained the TNFa binding ability of pro-In iximab which was pre-incubated with anti-Id Ab. In the future, we will be able to e ciently transform Abs into optimized pro-Abs to prevent the binding of anti-Id Ab using MSCS.…”
Section: Discussionmentioning
confidence: 99%
“…Further, pro-In iximab not only showed equivalent therapeutic e cacy to In iximab but also maintained immunity against Listeria infection in the RA mouse model, which led to a 71% survival rate compared to 0% of the In iximab treatment group, indicating that pro-Abs can enhance Ab selectivity and reduce side effects. [19] Our previous results showed that by using the concept of "copy and paste", we transformed almost 70% of therapeutic Abs into pro-Abs and achieved over 100-fold blocking ability compared to the parental Abs. Hence, this strategy could be further applied to develop customized pro-Abs.…”
Section: Introductionmentioning
confidence: 99%